Desenvolvimento de uma bebida alcoólica fermentada gaseificada do fruto do sapotizeiro (Manilkara zapota l.) - Cavalcante, Andressa Cláudia da Silva Santana (2022)
The processing of fruit to obtain beverages is a way to add value to the raw material, in addition to improving the producer's remuneration for the development of new products. Having this idea as a premise, the objective of this work was to elaborate and characterize carbonated fermented beverages based on sapodilla. With fruits acquired in the city of João Pessoa (PB), beverages were prepared from three different initial concentrations of total soluble solids (14 ºBrix, 16 ºBrix and 20 ºBrix). The analyzes performed were total titratable acidity, volatile acidity and fixed acidity, pH, total soluble solids, total dry extract, ash, reducing sugar, non-reducing sugar and total reducing sugar, total phenolic compounds, antioxidant activity, alcohol content and biomass concentration . For all formulations, fermentation kinetic parameters were calculated: product yield, cell yield, product productivity and fermentation efficiency. The data obtained were submitted to analysis of variance and the Tukey test was applied to identify significant differences between the means, at a confidence level of 95%. The aerated alcoholic fermented products from the three formulations showed average values of 7.4% v/v for alcohol content; 3.54 for pH; 2.2 ºBrix for the total soluble solids content and 145.20 meq/L for the total titratable acidity. The results of the kinetic parameters for the three formulations ranged from 0.28 to 0.34 for product yield, from 0.009 to 0.012 for cell yield, from 0.17 to 0.21 for product productivity and from 55 .56 to 67.30% for fermentation efficiency. For the content of total phenolic compounds, the formulation with 16 ºBrix presented the highest result, being 8.51 mg EAG/100 mL, with antioxidant capacity of 488.75 μM TEAC/g and DPPH radical inhibition, 596.04 μM TEAC/ g of ABTS radical inhibition and 705.24 μM TEAC/g of FRAP reducing power. The alcohol content parameter for all aerated sapodilla fermented products presented values within the range established by the brazilian legislation for fruit fermented, while for the total titratable acidity, the only fermented product that obtained a result within the specified by the legislation was the drink developed by the formulation with 20 ºBrix, with an average value of 122.4 meq/L.